Application of Humanistic Values in Islamic Education; The Challenges Of Human Potentials in Modern Era - Naufal Ahmad Rijalul Alam (Ta'allum: Jurnal Pendidikan Islam, 2016)
Education is a medium to change the characteristic of human beings to reach their perfection. In Islam, the ultimate goal of education is to uphold humanistic values thare embedded in every individual. This article attempts to analyse the application of Islamic concept of education by putting emphasis on the process of humanization. It is argued that the function of education is not only to provide cognitive knowledge for students, but alsoto introduce to the students humanistic values and principles. Humanitzation in Islamic education means that students are taught how to develop good character and personality. This is the challenge of development and progress in all lines of life that produces some of the social changes are large and comprehensive on human life and lead to social change. Education is charged on the human values of self learners Humanistic values that are embedded in Islamic education include: religious values, togetherness, and partnership.